Towards a socially sustainable world economy : an analysis of the social pillars of globalization - Torres, Raymond (ILO GenevaCH, 2001)
Reviews the international debate on globalization and proposes a simple definition. Identifies the indicators of increasing integration of national economies. Examines the possible relationship between different aspects of globalization such as trade, FDI and financial capital flows, on the one hand, and labour markets and income distribution, on the other. Examines the roles of social and labour policies, and related legislative and institutional reforms, for enhancing the benefits arising from globalization while reducing the social costs and facilitating the changeover to a more competitive international economy.